KONSEP DIRI PENDERITA HEMOFILIA DI PEKANBARU DALAM PERSPEKTIF FENOMENOLOGI - Abram, Abednego Tumei; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Hemophiliacs in Pekanbaru, with all the limitations that they have still capable to perform and complete their daily chores that require physical activity. For hemophiliacs, doing physical activity just like people in general will be harder, because when they do those physical activities, the joints in some parts of their body will ache and raise the bruises, this is caused by a lack of blood clotting factor. This study aims to determine the components of perceptual , conceptual component , the component attitudes, and communication experience hemophiliacs in PekanbaruThis study uses qualitative research methodology by conducting phenomenological approach. Subjects in this study consist of five people. Data collection techniques are grouped into three sections, which are; in-depth interviews, participant observation, and documentation. This study uses the Miles and Hubermen model of interactive data analysis system, by using the validity checking technique of the data through the extension of participation and triangulation.The result of this study showed that people with hemophilia in Pekanbaru if we look from the positive side of its perceptual components are just like people in general, they are cheerful, comfortable with their environment and there is no sense of shame, while its negative side is they sometimes less grateful and feel embarrassed. In the view of the positive side of its conceptual components, hemophilia sufferers tend to be responsible, humorous, rarely feel sad and often confident, but its negative side can be seen from a more reserved attitude. Then, focusing on the attitude component, the positive side which is owned by hemophiliacs is their friendly act, pleasant and helpful, but the fear of being alienated is the negative side of the patient. Meanwhile, based on the experience of communication, hemophiliacs in Pekanbaru have been able to implement a good and pleasant communication such as a sense of pride and pleasure, acceptance and friendship and more attention from the family, but there is a little less pleasant communication experience such as a fear of the opposite sex, discrimination and verbal or non-verbal harassment.Keywords: Self-concept, phenomenology, and hemophili